Strength and Stiffness Parameters of an Unsaturated Tropical Soil - Fernandes, Jeferson B. [UNESP]; Rocha, Breno P.; Rodrigues, Roger A. [UNESP]; Giacheti, Heraldo L. [UNESP] (American Society of Civil Engineers (ASCE), 2018)
The interpretation of in-situ tests for site characterization of unsaturated tropical soil sites should consider both the spatial and the seasonal variability caused by the soil suction on the strength and stiffness parameters. This paper presents and discusses the suction-controlled and conventional triaxial with bender elements and in-situ tests data together with water content profiles, as well as soil water retention curves (SWRC) from an unsaturated tropical sandy soil site, to examine the influence of the soil suction on the strength and stiffness soil parameters. The results showed the influence of soil suction on the data interpretation of CPT and DMT to define strength and stiffness parameters for the top layer. This paper point out the importance of considering the seasonal variability caused by suction on the characterization of the study site.
Keywords: In-situ and laboratory tests; Site investigation; Soil water retention curve; Tropical soil; Unsaturated soil